IMPLEMENTASI LAGU EDUKASI ANTI BULLYING UNTUK PERILAKU PROSOSIAL ANAK USIA 5-6 TAHUN DI TK IT RAUDHATUL JANNAH CILEGON, BANTEN - Hermas Syaripah Huban; Siti Khosiah; Fahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the emergence of less prosocial behavior among early childhood learners, such as mocking friends, fighting over toys, and difficulties in cooperating. The study aimed to describe the implementation of anti bullying educational songs for prosocial behavior in children aged five to six years at TK IT Raudhatul Jannah Cilegon, Banten. This study used a qualitative method with a descriptive approach. The research subjects were group B teachers. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of anti bullying educational songs was carried out through planning, implementation, and evaluation stages. Educational songs were used as learning media to develop prosocial behavior such as respecting others, helping friends, cooperating, apologizing, and using polite words. Teachers acted as facilitators, guides, motivators, and role models during the learning process. The implementation of anti bullying educational songs had a positive influence on the development of children’s prosocial behavior through enjoyable and interactive learning activities.